The Study of the Impact of Empowering Leadership on Adaptive Performance of Faculties Based on Chain Mediating - Xu, Ying; Zhang, Mengliu (Frontiers in Psychology, 2022)
High-quality faculties are the fundamental guarantee to achieving the connotation development of higher education. Hence, performing university faculties determines the quality of teaching and the level of talent cultivation. Facing the change in teaching demand and environment, faculties need to change their working methods spontaneously to achieve high-level performance. Relevant empirical studies have shown that empowering leadership positively affects adaptive performance. However, some researchers have found that leadership effectiveness even has a negative effect. There may be two reasons for the inconsistency in the effectiveness of empowering leadership: (1) There is a lack of in-depth research on the effectiveness of empowering leadership and employees’ performance in existing studies, and the exploration of its theoretical mechanism should be enriched. (2) The effectiveness of empowering leadership may be subject to the conditions of the individual’s characteristics of the empowering. Therefore, the mechanism of empowering leadership on faculties’ adaptive performance still needs to be further explored. This study explores the impact of empowering leadership on adaptive performance. Based on Social Exchange Theory and Psychology Empowerment theory, this study explores the mediating role of the leadership-member exchange relationship and psychological empowerment in the relationship between them. According to Regulatory Focus Theory, the moderating role of promotion focus and prevent focus was studied. We adopted questionnaire survey data including 292 individuals in Changchun, Shijiazhuang, and other cities; STATA 15 was conducted to test the hypotheses. The results showed that: (1) Empowering leadership was significantly and positively related to adaptive performance. (2) Leader-member exchange relationship and psychological empowerment play a mediating chain role in empowering leadership and adaptive performance; empowering leadership promotes psychology empowerment by enhancing the leadership-member exchange relationship, enhancing their adaptive performance. (3) Promotion focus positively regulates the relationship between psychological empowerment and adaptive performance. Individuals with a promotion focus have a significant positive impact on adaptive performance. Individuals with preventing focus do not weaken the positive impact of psychological empowerment on adaptive performance.